Which Integration Policies Work? The Heterogeneous Impact of National Institutions on Immigrants' Labor Market Attainment in Europe - Lucinda Platt; Javier Polavieja; Jonas Radl (International Migration Review, 2022)
Can specific policies support the economic integration of immigrants? Despite the crucial importance of this question, existing evidence is inconclusive. Using data from the European Social Survey, we estimate the effects of integration and anti-discrimination policies, alongside social expenditure and labor market regulation, on the labor market performance of 6,176 non-European immigrants across 23 European countries. We make three contributions: 1) we investigate the distinct role of discrete policy areas for labor market integration outcomes, 2) we allow for heterogeneous effects of policies on immigrants with different characteristics, and 3) we examine immigrants' occupational attainment while accounting for their selection into employment. We find that immigrants' employment chances are negatively associated with national levels of expenditure on welfare benefits but positively associated with policies facilitating immigrant access to social security. We also find that labor market rigidity is negatively associated with immigrants' occupational attainment, but we find little evidence that policies aimed at supporting the transferability of immigrants' qualifications promote their occupational success. Our results strongly suggest that anti-discrimination policies are important for immigrant economic integration. Yet while these policies are associated with greater occupational success for all female immigrants, they seem to be only positively associated with the occupational attainment of higher-skilled and non-Muslim immigrant men. As this article suggests, anti-discrimination policies can foster immigrants' labor market success, yet these policies currently fail to reach those who face the strongest anti-immigrant sentiments — that is, unskilled male immigrants and Muslim immigrant men.
doi:10.25384/SAGE.15094367.v1
Keywords: 300; immigrants; occupational attainment; employment; Europe; integration policies; social expenditure; labor market regulations